Two new species of the genus Pristaulacus (Hymenoptera, Evanioidea, Aulacidae) from Japan - Konishi, Kazuhiko; Matsumoto, Rikio (Zootaxa, 2019)
Two new species of the genus Pristaulacus, P. ohishii sp. nov. and P. uenoi sp. nov. are described from Japan. The former species belongs to the comptipennis species group in having the strongly concaved occipital margin, and is peculiar in the species group in having the combination of the interrupted occipital carina and a broadly rounded and shallow occipital medial groove. The latter species resembles P. ryukyuensis in having the occipital carina not interrupted, the anterior margin of mesoscutum in lateral view acute and veins M+Cu, r-m and Cu of hind wing not pigmented, but they can be easily distinguished by the coloration of mesosoma and the dark spots of fore wing.